The competence model of a talented manager ("Journal "U". Economy. Management. Finance.", 2023)
The article examines the competencies of a talented manager, as well as the importance of a talented manager in modern organizations. A talented manager plays an important role in every organization, since only a talented manager is able to competently manage talented employees. The purpose of this article is to study the concept of a "talented leader", as well as to consider the competencies that a talented leader should have.
Keywords: competencies; talented manager; competence development